Idiosyncrasies of the oligarchic elite: On the political economy of wealth concentration in Austria - Stephan Pühringer; Matthias Aistleitner; Lukas Cserjan; Sophie Hieselmayr; Jakob Weber (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2025)
The increasing concentration of income and wealth on the national and international level is a topic that has received increased attention both in social science research as well as public policy debates. While data availability is a well-known and often-lamented problem in wealth studies, especially the group of HNW-households remains largely unexplored. In this study, we aim to contribute to a deeper understanding of the impact of HNW-households and their networks on current wealth distributions. Based on an extensive data set of company ownerships of a sample of the 62 wealthiest Austrian HNW-households, we apply a social network analysis of two-mode networks (institutions & persons) to highlight networks of corporate ownership and (indirect) control. An overall finding is that numerous HNW-networks involve a multitude of legal entities, creating complex and opaque control structures that complicates the tracing of economic ownership. Besides this, our findings show several idiosyncrasies of the super-rich.
Keywords: 330; Super-rich; High Net Worth individuals and families; Wealth Concentration; Social Network Analysis; Austria